دراسة وحساب البارامترات المؤثرة على حركة السيارة, وتماسك العجلات مع سطح الطريق - هيام وظيف حسن (Tishreen University, 2014)
تزداد صناعة السيارات في الوقت الحاضر تواقاً مع زيادة الطلب على نقل الركاب والحمولات, وتسعى الشركات الصانعة إلى توفير الاستقرار والانسيابية لحركة السيارات وإمكانية توجيهها في الظروف والأنظمة المختلفة لاستثمارها, وهنا تلعب أنظمة التعليق والتوجيه الدور الأكبر في تحقيق تلك المتطلبات؛ لذلك يهدف  هذا البحث إلى وضع طريقة لاختيار المميزات المثلى لأنظمة التعليق ودراسة ردود الأفعال على الدواليب الموجهة للسيارة. تبين من خلال البحث أن لمؤشرات العناصر المرنة والمخمدة في أنظمة التعليق دوراً كبيراً في تقليل الاهتزازات الحاصلة، وفي المحافظة على تماسك العجلات مع سطح الطريق, كما تبين أن زيادة القوى المؤثرة المتعلقة بتوجيه السائق للعجلات تؤدي الى نشوء عزوم انعطاف للسيارة حول محورها خصوصاً عند عدم انتظام عملية الفرملة على الدواليب. At present time the cars manufacturing increase the compatibility with the maximum demand on passengers and load transmission, the manufacturing companies involved to make the stability and smooth cars movement available and the ability of it's orientation in proper direction in various circumstances and systems to invest the same. The direction and  suspensions systems are playing the main role to achieve  these requirement , Hence, the research purposed to put a way for choosing the optimal characteristics of suspensions systems  and studying the reaction on the car wheels. This paper shows that the proportion of elastic and slowdown of elements in suspensions systems  own a big role in reducing the happening vibrations which saving the wheels steady on road surface, and  it's show also that the increasing of impact forces relevant to direct the driver by the wheels leading  into creating turning moments of the car around  it's axis, particularly when the breaking process of wheels is not regular.